PENGARUH PENGGUNAAN MEDIA FILM ANIMASI TERHADAP KREATIVITAS MENGGAMBAR ILUSTRASI PADA PEMBELAJARAN SENI RUPA - Apriyani, Cica Kurnia Fitri; Julia, Julia; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
Learning proccess without media causing a lack of drawing creativities development of students, so they can’t brings up their creative ideas. That case encourage the researcher to apply animated movies as a learning alternative media to stimulate their creativities. The aim of this research is to test animated movies usage as a learning alternative media. This research included into nonequivalent control group of quasi experimental design. The sample are taken from purposive sampling technique. The researcher got the data by test, observation, interview, and questionnaire. The analysis data which used is Shapiro-Wilk (normality), Levene (homogeneity), and free t sample (average difference test). The research result shows significant differences about student creativities between experiment class and control class. The calculation results using free t sample test, obtained P-value (sig. 2-talled) amounting to 0,00 which is H0 received. So it can be concluded that animated movies usage more effective to improve student creativities in illustrations drawing.